2007
DOI: 10.1177/0963662506065558
|View full text |Cite
|
Sign up to set email alerts
|

Understanding citizen perceptions of science controversy: bridging the ethnographic—survey research divide

Abstract: Using the contemporary debate in the United States over embryonic stem cell research as a test case, we outline a theoretical framework that points to the central impact of value predispositions, schema, political knowledge, and forms of mass media use in shaping public perceptions of science. In the process, by proposing an alternative approach to the dominant science literacy model, we address the existing divide between survey-based and ethnographic studies. Analyzing nationally representative survey data c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
142
2
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(159 citation statements)
references
References 43 publications
13
142
2
2
Order By: Relevance
“…Numerous previous studies have found some extent of empirical co-occurrence of media content/media use and public understanding of GM crops or other kinds of biotechnologies (Bauer, 2002(Bauer, , 2005aBesley & Shanahan, 2005;Ho et al, 2008;Hornig Priest, 1994;Hughes et al, 2008;Liu & Priest, 2009;Nisbet & Goidel, 2007;Stewart et al, 2009;Vilella-Vila & Costa-Font, 2008;Wagner & Kronberger, 2001;Wagner et al, 2002). The present paper intended to contribute to this body of literature among others by providing a case study from a country where the issue of GM crops was of lower salience in the media and lower on the public agenda than in the societies on which the earlier studies had focused.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous previous studies have found some extent of empirical co-occurrence of media content/media use and public understanding of GM crops or other kinds of biotechnologies (Bauer, 2002(Bauer, , 2005aBesley & Shanahan, 2005;Ho et al, 2008;Hornig Priest, 1994;Hughes et al, 2008;Liu & Priest, 2009;Nisbet & Goidel, 2007;Stewart et al, 2009;Vilella-Vila & Costa-Font, 2008;Wagner & Kronberger, 2001;Wagner et al, 2002). The present paper intended to contribute to this body of literature among others by providing a case study from a country where the issue of GM crops was of lower salience in the media and lower on the public agenda than in the societies on which the earlier studies had focused.…”
Section: Discussionmentioning
confidence: 99%
“…A number of researchers from other countries have reported some kind of empirical relationship between media use and public understanding of biotechnologies -including GM as well as the red-green biotechnology distinction -even if not necessarily all media variables were significant, and even if differences were found between countries (Bauer, 2002(Bauer, , 2005aBesley & Shanahan, 2005;Ho, Brossard, & Scheufele, 2008;Hornig Priest, 1994;Hughes et al, 2008;Liu & Priest, 2009;Nisbet & Goidel, 2007;Stewart, Dickerson, & Hotchkiss, 2009;Vilella-Vila & Costa-Font, 2008;Wagner & Kronberger, 2001;Wagner, Kronberger, & Seifert, 2002). Many of these previous studies have concentrated on societies where there has been heated public debate on the GM controversy (Hughes, Kitzinger, & Murdock, 2008).…”
Section: Relationship Between the Two Arenasmentioning
confidence: 99%
“…Sometimes education is used as a proxy for science knowledge, other times in combination with direct measures. Attitudes to stem cell research, for example, are positively associated with level of education (Nisbet & Goidel, 2007), issue-specific awareness (Nisbet, 2005) and attention to media reports of scientific issues (Ho et al, 2008 ;Nisbet & Goidel, 2007). Education has also demonstrated a significant positive association with openness to prenatal genetic testing (Singer et al, 1999) and pessimism about biotechnology (Simon, 2010 (Brossard & Nisbet, 2007 ;Popkin, 1991) and motivated reasoning (Kahan et al, 2008).…”
Section: Scientific Knowledgementioning
confidence: 99%
“…Deficit model thinking assumes that facts speak for themselves and have to be interpreted by all citizens in similar ways, otherwise irrational public beliefs are invoked [116]. In the case of the CVC strain in the US, as well as many other plant pathogens worldwide, interpretation of "facts" by citizens-or, more appropriately, biological observation-were similar, generally accepting scientists' findings or international guidelines about plant protection.…”
Section: Discussionmentioning
confidence: 99%